Analisis Pola Penjualan Obat di Apotek Menggunakan Algoritma Apriori Untuk Optimalisasi Stok dan Penjualan - Yulindawati, Yulindawati; Yusnita, Amelia; Mayasari, Renni; Melano, M Erick (TIN: Terapan Informatika Nusantara, 2024)
This research aims to identify product sales patterns at Teluk Bayur Pharmacy to optimize stock management and increase sales by using data mining techniques, especially the Apriori Algorithm. Pharmacies are very instrumental in providing drug-related information and are a form of retail trade that sells medicines at more affordable prices compared to hospital services. However, Teluk Bayur Pharmacy often faces difficulties in managing stock, analyzing product sales patterns and consumer behavior, which causes problems of over stock or under stock. Through the application of Association Rule Mining using the Apriori Algorithm, this research analyzes the correlation between products to find frequent purchase patterns. The methods used include literature study, data collection, data preprocessing, application of Apriori Algorithm, evaluation and interpretation of results, and application of conclusions and recommendations. To analyze sales patterns, the data collected exceeded 100 entries, and 12 transactions were selected that represented the most sales each month. The results of testing the analysis utilizing tanagra 1.4.41 software, by setting a minimum support of 40% and a minimum confidence of 70%, from the results of research and testing show that products that are often purchased together by customers are masks, vegeta, and antimo with a confidence value above 70%. The findings are expected to provide insight for Teluk Bayur Pharmacy in understanding consumer behavior and identifying new sales opportunities.